Women Entrepreneurship Development in Small Scale Sector in the Context of Globalisation - D, Himachalam; M., Shankara (Ushus Journal of Business Management, 2003)
With the impetus on entrepreneurial development in semi-urban and rural areas to solve the threatening unemployment crisis, women entrepreneurs have a major role to play. Women are found equally capable and given the right encouragement and support, they are bound to contribute in abundance towards the upliftment of the small scale and tiny sector.